Multidisciplinary Da’wah Communication Strategy: Integrating Digital Media, Psychological Approaches, and Islamic Values in Mitigating Online Gambling Hazards - Mohammad Rofiq; Samsuriyanto Samsuriyanto (Neo Journal of economy and social humanities, 2026)
The objective of this research is to formulate a multidisciplinary da’wah communication strategy by integrating digital media, psychological approaches, and Islamic values to mitigate the hazards of online gambling. Unlike previous studies that focus on singular approaches, this research proposes an original integrative model specifically designed to address the challenges of 2026, where gambling platforms utilize highly aggressive and hyper-personalized algorithms. This study employed a library research method with a qualitative-descriptive approach. Data were systematically collected from primary and secondary sources, including 2026 digital industry trends, psychological literature, and theological foundations. The data analysis followed an interactive model involving data condensation, data display, and conclusion drawing. The results indicate that an effective mitigation strategy requires precise audience segmentation and the utilization of interactive technology, such as gamification, to counter AI-driven gambling algorithms. The study finds that this original synthesis—combining empathy-based psychological interventions with “sticky narratives”—is more effective in motivating behavioral change among digital-native addicts compared to traditional normative prohibitions. Furthermore, the synergy between the theological principles of maysir prohibition and digital literacy creates a robust, systemic social defense. In conclusion, this multidisciplinary framework provides a practical and pioneering guide for preachers and educators to conduct humane and relevant behavioral interventions amidst the rapid technological developments of 2026.